Vibration measurements on small to medium single-span railway bridges - Rebelo, C. (2012)
Due to the need for increasing train speeds several existing small to medium span bridges in the track Linz-Wels (Austria) were re-evaluated. In a preliminary numerical calculation, considering conservative values for the dynamic parameters, very high vertical accelerations were computed for some of those structures. An experimental program was thus carried out in order to get a better estimation for the dynamic behaviour of the bridges, concerning mainly the first vertical eigenfrequency and the corresponding viscous damping. The paper reports on the results of this experimental investigation and identifies some areas where further research is necessary.